2021
DOI: 10.1155/2021/8470944
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis and Intervention of Factors Affecting Abnormal Postpartum Glucose Tolerance and Gestational Recurrence in Gestational Diabetes

Abstract: ObjectiveTo investigate the influencing factors of abnormal postpartum glucose tolerance and pregnancy recurrence in gestational diabetes mellitus (GDM) and to develop reasonable interventions to prevent postpartum glucose tolerance and recurrence of pregnancy. Methods. Retrospective analysis of clinical data of 238 GDM patients during pregnancy, including age, body mass index (BMI) before and after pregnancy, regular exercise during pregnancy, insulin use, family history of diabetes, fasting blood glucose (FP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Moreover, postpartum screening of pGDM patients remains inadequate, necessitating the development of an efficient and easy-to-implement tool that can include both panel genes and metabolic profile analysis to identify patients at high risk for DM and CVD that require more in-depth medical supervision. Earlier research showed that elevated cardiovascular risk in pGDM females in the postpartum period results from an interaction of genetic predisposition and diet [ 37 ].…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…Moreover, postpartum screening of pGDM patients remains inadequate, necessitating the development of an efficient and easy-to-implement tool that can include both panel genes and metabolic profile analysis to identify patients at high risk for DM and CVD that require more in-depth medical supervision. Earlier research showed that elevated cardiovascular risk in pGDM females in the postpartum period results from an interaction of genetic predisposition and diet [ 37 ].…”
Section: Pregnancy Complicationsmentioning
confidence: 99%
“…In contrast, minimum-contact home-based interventions are more commonly used in prenatal interventions as they are easier to implement for pregnant women than structured exercise programs [10]. Many women with GDM prefer not to exercise despite the potential bene ts because of a variety of barriers, including a lack of time, child care commitments, exhaustion, and a lack of access to exercise equipment [12]. As a result, by offering an attractive and familiar atmosphere, a supervised homebased exercise training program may be a promising way to encourage exercise adherence and remove barriers to exercise [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many women with GDM prefer not to exercise despite the potential bene ts because of a variety of barriers, including a lack of time, child care commitments, exhaustion, and a lack of access to exercise equipment [12]. As a result, by offering an attractive and familiar atmosphere, a supervised homebased exercise training program may be a promising way to encourage exercise adherence and remove barriers to exercise [11,12]. There are few research examining the e cacy of guided home exercise plans for treating GDM.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%